GENERASI Z DAN PENUNDAAN PERNIKAHAN PERSPEKTIF HUKUM ISLAM: STUDI KASUS DI KECAMATAN SIMPUR - sahibul ardi; Rina (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This research was motivated by the increasing number of young people, especially Generation Z, who chose to delay marriage. This was reflected in studies showing that most of Generation Z did not consider marriage a top priority. This study aimed to examine Generation Z’s views on delaying marriage and the factors that encouraged them to do so, analyzed from the perspective of Islamic law. This research was a legal psychology study. The subjects were members of Generation Z residing in Simpur District who held views related to delaying marriage. The object of the study was Generation Z’s perspectives on the decision to delay marriage from the perspective of Islamic law, including the influencing factors, examined through interview and documentation techniques. Using a qualitative descriptive approach, the results showed that Generation Z viewed delaying marriage as not contrary to Islamic teachings, as long as the underlying reasons were strong and did not violate sharia, such as preparing financial, mental, and educational preparedness, or because they had not yet found a suitable partner. In Islamic law, delaying marriage is permissible as long as it does not cause harm and is carried out while maintaining oneself from actions prohibited by religion. Thus, the postponement of marriage by Generation Z in Simpur District was a form of effort (ikhtiar) to prepare for a more mature and responsible marriage in accordance with the values of Islamic teachings. Keywords: Generation Z, Delayed Marriage, Islamic Law.